Differential recurrence after laparoscopic incisional hernia repair: importance of a nationwide registry‐based mesh surveillance. Issue 9 (1st April 2020) - Helgstrand, F.; Thygesen, L. C.; Bisgaard, T.; Jørgensen, L. N.; Friis‐Andersen, H.
Abstract : Background: Identification of suboptimal mesh products is essential to improve the outcome after hernia surgery. This study investigated whether a national clinical database combined with administrative registries may serve as a tool for postmarketing evaluation of mesh products for hernia surgery. Methods: This was a propensity score‐matched case–control cohort study comparing outcomes in patients undergoing laparoscopic incisional hernia repair with either one particular mesh or any other synthetic mesh. Data on patients registered in the Danish Ventral Hernia Database between 2010 and 2016 were combined with administrative data from the Danish National Patient Registry. The primary outcome was operation for recurrence. Secondary outcomes were 30‐day readmission, 30‐day reoperation for complications (excluding hernia recurrence), and mortality after 30 and 90 days. Results: In total, 740 patients who underwent repair with one particular mesh were matched with 1479 patients who received any other synthetic mesh. The rate of repair for hernia recurrence was significantly higher in the particular mesh group than in the reference group: 12·8 versus 6·3 per cent respectively (hazard ratio 2·09, 95 per cent c.i. 1·57 to 2·79; P < 0·001). Use of the particular mesh increased the risk of readmission (odds ratio (OR) 1·53, 1·16 to 2·01; P = 0·002) and reoperation for a complication (OR 1·60, 1·03 to 2·47, P = 0·030). No difference in mortality was found. Conclusion: Clinical registries with prospectively collected data can provide long‐term surveillance of commercial mesh. Laparoscopic incisional hernia repair with one particular mesh was associated with an increased rate of short‐term complications and double the risk of repair for recurrence. Abstract : This study showed that clinical registries with prospectively collected data can provide long‐term surveillance of commercial mesh. Laparoscopic incisional hernia repair with a Physiomesh® was associated with double the risk of late recurrence repair and an increased rate of short‐term complications. Good use of registries Abstract : Antecedentes: Es esencial identificar los productos subóptimos referidos a las mallas para mejorar los resultados en la cirugía de la hernia. Este estudio analizó si un registro clínico nacional combinado con registros de bases de datos administrativos puede servir como herramienta para la evaluación post‐comercialización de productos de mallas para cirugía de la hernia. Métodos: Se efectuó un estudio de emparejamiento por puntaje de propensión de una cohorte de casos y controles en el que se comparaban los resultados de la malla Physiomesh® frente a cualquier otra malla sintética en pacientes sometidos a una reparación laparoscópica de una eventración. Se combinaron los datos de los pacientes del registro danés de hernia entre 2010 y 2016 con los datos administrativos del registro nacional de pacientes de Dinamarca. La variable principal fue la reintervención por recidiva. Las variables secundarias fueron el reingreso a 30 días, la reoperación a 30 días por complicaciones (excluyendo la recidiva de la hernia) y la mortalidad a 30 y 90 días. Resultados: Para la reparación herniaria se utilizó la malla Physiomesh® en 740 pacientes, que se emparejaron mediante el análisis por puntaje de propensión con 1.479 pacientes en los que se colocó otra malla sintética. La reintervención por recidiva herniaria fue significativamente mayor en el grupo Physiomesh® (12, 8%) que en el grupo de referencia (6, 3%); cociente de riesgos instantáneos ( hazard ratio, HR): 2, 09 (i.c. del 95%: 1, 57‐2, 79), P < 0, 001. El riesgo de reingreso (razón de oportunidades, odds ratio, OR: 1, 53, 1, 16‐2, 01, P = 0, 002)) y de reoperación por una complicación (OR: 1, 60, 1, 03‐2, 47, P = 0, 030) fueron superiores en el grupo Physiomesh®. No hubo diferencia en la mortalidad. Conclusión: Los grandes registros clínicos con datos recogidos de forma prospectiva pueden ser útiles para efectuar el seguimiento a largo plazo de una malla comercializada para garantizar la seguridad del producto y su calidad quirúrgica. La reparación laparoscópica de una eventración con la malla Physiomesh® se asociaba con un riesgo doble de recidiva y un aumento de la tasa de complicaciones a corto plazo.